PANDANGAN RESPONDEN MAHASISWA UPNVJ DALAM MENYIKAPI PERGANTIAN GUBERNUR DKI JAKARTA DENGAN PENJABAT GUBERNUR AKIBAT ADANYA KEKOSONGAN JABATAN - Andini Lutfiah Putri (2023)
Each region holds regional elections every five years to elect its regional head. However, based on the Elections Law, in 2024 the regional elections will be held simultaneously with the National Elections, resulting in the vacancy of the position of Regional Head from 2022 to 2024. One of the affected areas is DKI Jakarta. Filling the vacancy in the position of Governor of DKI Jakarta with the Acting is a political issue that is being debated. Community involvement in the appointment process was minimal, leading to various responses and speculations from the public. The appointment of public officials without public participation is contrary to the principles of democracy and good governance which prioritizes people's participation as power holders. This study aims to find out the views of UPNVJ Student Respondents in responding to the replacement of the Governor of DKI Jakarta with the Acting Governor based on the principles of good governance. This research uses a mixed method, which uses quantitative and qualitative methods. Respondents as many as 100 UPNVJ students domiciled in DKI Jakarta were selected using the non-probability sampling method, which is purposive sampling from a total population of 5701 students. This method involves the stages of interviews and library research as part of qualitative methods, as well as the distribution of questionnaires in the form of g-form as a quantitative data collection process to validate findings from qualitative research. The results of this study show: First, based on quantitative and qualitative data, the filling of positions by the Acting Governor of DKI Jakarta has not fulfilled the principles of transparency and democracy. Second, there are doubts about the implementation of the principles of accountability and good governance in filling the position, which is supported by quantitative and qualitative data findings. Third, based on quantitative data, respondents reported a lack of places for the public to express opinions and a lack of information disclosure, while qualitative data confirmed a lack of information disclosure and encouraged the dissemination of information through electronic and print media. Fourth, the majority of respondents agreed that the filling of positions is lawful, as seen in quantitative and qualitative data. Fifth, UPNVJ students support the filling of positions by PJ Governor to maintain smooth local government. The results of quantitative and qualitative research support each other, showing consistency in UPNVJ students' views on PJ Governor in achieving sustainable development and responsive to community demands. Keywords: Pilkada 2024, Vacant Position, Acting Governor, Good Governance